2022
DOI: 10.3390/molecules27217462
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New 2,3-Dihydroindole Derivatives and Evaluation of Their Melatonin Receptor Binding Affinity

Abstract: 2,3-Dihydroindoles are promising agents for the synthesis of new compounds with neuroprotective and antioxidant properties. Usually, these compounds are obtained by direct reduction of the corresponding indoles containing acceptor groups in the indole ring for its activation. In this work, we propose a synthetic strategy to obtain new 2,3-dihydroindole derivatives from the corresponding polyfunctional 2-oxindoles. Three methods were proposed for reduction of functional groups in the 2-oxindole and 2-chloroindo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Meanwhile, the 2,3-Dihydroindoles represent a group of promising agents that exhibit neuroprotective and antioxidant properties. Herein, Volkova et al have reported the synthesis of new 2,3-dihydroindole derivatives as potential melatonin receptor ligands [ 5 ]. The research team used several boron hydrides to reduce the functional groups within 2-oxindole and 2-chloroindole molecules, and they proposed that a NaBH 4 /NiCl 2 reagent led to cyano-group reduction while BH 3 -based reagents produced simultaneous reductions in both cyano- and amido-groups of the oxindole ring.…”
Section: Active Pharmacological Constituents and Their Derivates For ...mentioning
confidence: 99%
“…Meanwhile, the 2,3-Dihydroindoles represent a group of promising agents that exhibit neuroprotective and antioxidant properties. Herein, Volkova et al have reported the synthesis of new 2,3-dihydroindole derivatives as potential melatonin receptor ligands [ 5 ]. The research team used several boron hydrides to reduce the functional groups within 2-oxindole and 2-chloroindole molecules, and they proposed that a NaBH 4 /NiCl 2 reagent led to cyano-group reduction while BH 3 -based reagents produced simultaneous reductions in both cyano- and amido-groups of the oxindole ring.…”
Section: Active Pharmacological Constituents and Their Derivates For ...mentioning
confidence: 99%
“…Recently, considerable attention has been paid to melatonin and dopamine receptors as promising targets in the search for antiglaucoma drugs [ 17 , 18 ], which causes interest in oxindole derivatives as well. Previously, we have observed that 2-oxindole derivatives can reduce IOP in animal models and have antioxidant properties [ 19 , 20 , 21 , 22 , 23 ]. The most promising were recognized as 3-hydroxy-2-oxindoles.…”
Section: Introductionmentioning
confidence: 99%